Pelatihan Kepemanduan di Desa Wisata Donokerto - Setiaji, Yudi; Wahyono, Mohammad Hardi; Santosa, Santosa (Jurnal ABDIMAS PARIWISATA, 2020)
Donokerto village is one of the pioneering tourist villages that has good potential in terms of diversity of tourist attractions. As a Pioneer tourism village, the village of Donokerto requires qualified human resources for tourism services, especially as a tour guide. Therefore, the AMPTA Yogyakarta Tourism School in collaboration with PUM Netherlands Senior Experts held a community service with the theme "Guiding Training in Donokerto Village". This community service activity is carried out using role play and simulation methods, namely by trying to directly deal with tourists and service instructors providing evaluations. The recommendation from this service activity is to increase the ability of foreign languages and public speaking for the community as potential tour guides